Levelling off of prevalence of obesity in the adult population of Sweden between 2000/01 and 2004/05 - Johansson Sven-Erik; Sundquist Jan; Sundquist Kristina (BMC, 2010)
Abstract Background The escalating global epidemic of obesity is of worldwide concern because of its association with several chronic diseases and premature mortality. Some subgroups seem to be more affected than others. The aim of this study was to examine whether the mean BMI (adjusted for age) and the prevalence of obesity (adjusted for all the explanatory variables) changed between 2000/01 and 2004/05 in different subgroups of the Swedish population. Methods This study compared two cross-sectional, nationwide random samples of persons aged 16 to 84 years: the first from 2000/01 (5515 men, 5838 women) and the second from 2004/05 (4681 men, 4821 women). After stratification by gender, a logistic regression model was applied to analyse possible changes in mean BMI and the prevalence of obesity between 2000/01 and 2004/05. Results Total mean BMI remained almost unchanged between 2000/01 and 2004/05 for both men and women. The prevalence of obesity increased slightly in both men and women, but not significantly (from 9.7 to 10.8% and from 9.6 to 10.2%, respectively). The prevalence of obesity in 2004/05 was especially high in some subgroups: men aged 45-54 (14.3%) or 55-64 (16.5%), women aged 65-74 (15.9%) or 75-84 (16.8%), men and women of middle educational level (15.6% and 14.4%, respectively), male former smokers (13.4%), and men from small towns or rural areas (13.1%). Conclusions Although the mean BMI and obesity were almost unchanged in the Swedish adult population between 2000/01 and 2004/05, obesity levels in Sweden remained unacceptably high, especially in certain subgroups. Primary and secondary intervention actions should strive to decrease the prevalence of obesity in Sweden.